Implementation of the AUA Castration Resistant Prostate Cancer Guidelines into Practice: Establishing a Multidisciplinary Clinic. Issue 3 (May 2016) - Stratton, Kelly L.; Moeller, Abby M.; Cookson, Michael S.
Abstract : Introduction: : AUA (American Urological Association) published guidelines on the treatment of castration resistant prostate cancer in August 2013. Urologists have remained integral members of a multifaceted team of professionals treating patients with prostate cancer. We discuss approaches to implementing a guidelines based, multidisciplinary, advanced prostate cancer treatment clinic. Methods: : A supplemented PubMed® search was performed to identify published literature evaluating the treatment of castration resistant prostate cancer. Attention was placed on studies assessing a multidisciplinary approach to treating patients with castrate resistant prostate cancer. A review of currently approved agents is provided with emphasis on administration from an integrated clinic. Results: : Treatment of patients with advanced prostate cancer remains a significant function of many urology clinics. Guidelines assist urologists with providing patients with the most appropriate care along with multispecialty collaboration. Several organizational approaches have been attempted, including all‐in‐one clinics, onsite clinics and virtual multidisciplinary clinics. Through close collaboration with medical oncologists, radiation oncologists and support staff patients with advanced prostate cancer can obtain the highest quality care. Conclusions: : Urologists remain an integral member of the multidisciplinary approach to treating castrate resistant prostate cancer. AUA guidelines for castration resistant prostate cancer are a useful tool that can be incorporated into virtual multidisciplinary clinics. Through a team approach patients receive timely and appropriate care.